2010
DOI: 10.2478/v10042-010-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in the developing chicken cornea following caffeine administration.

Abstract: Caffeine is one of the most frequently consumed psychoactive substances. It has been known for many years that caffeine at high concentrations exerts harmful effects on both women's and laboratory animals' fertility, moreover it may impair normal development of many organs in the prenatal period. So far there have been few studies performed that demonstrate teratogenic effects of caffeine on structures of the developing eye, particularly the cornea. The aim of the study was to show ultrastructural changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Kujawa-Hadryś et al. demonstrated that caffeine causes changes of collagen fiber pattern in Bowman's membrane and corneal stroma 26 and decreases the total thickness of developing chick embryo cornea 27 . Evereklioglu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Kujawa-Hadryś et al. demonstrated that caffeine causes changes of collagen fiber pattern in Bowman's membrane and corneal stroma 26 and decreases the total thickness of developing chick embryo cornea 27 . Evereklioglu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have found that caffeine, when applied topically, prevents apoptosis and removes reactive oxygen species in lens, thus having anticataractogenic effect [ 20 , 21 ]. Moreover, it has been demonstrated that administration of caffeine causes changes of collagen fibers of Bowman's membrane and corneal stroma along with alterations in the amount of collagen fibers and stromal cells in developing chicken corneas [ 22 ]. Evereklioglu et al [ 23 ] have shown that high dose of caffeine administration to pregnant rats leads to histopathological changes in the cornea of newborn rats including vacuolated endothelial cells with proliferation, hyperchromasia, polymorphism, endothelial cell agenesis, increased stromal mitotic activity, and focal increase in corneal thickness with widely separated corneal lamellae.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the orbital bone, which is the accessory structure of the eye, was deficient after caffeine treatment. It has been reported that excess caffeine causes changes to the cornea and the failure of neural tube closure because of excessive neuroepithelial cell proliferation . In rat embryos, up to 91% of the caudal neural tubes failed to close following caffeine treatment .…”
Section: Discussionmentioning
confidence: 99%